2017
DOI: 10.1080/15384101.2017.1325046
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of the imipridone family, analogs of clinical stage anti-cancer small molecule ONC201, reveals potent anti-cancer effects of ONC212

Abstract: Anti-cancer small molecule ONC201 upregulates the integrated stress response (ISR) and acts as a dual inactivator of Akt/ERK, leading to TRAIL gene activation. ONC201 is under investigation in multiple clinical trials to treat patients with cancer. Given the unique imipridone core chemical structure of ONC201, we synthesized a series of analogs to identify additional compounds with distinct therapeutic properties. Several imipridones with a broad range of in vitro potencies were identified in an exploration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 16 publications
7
81
0
Order By: Relevance
“…Dose-response curves of NALM-6 in the presence of ONC201 or ONC212 were generated to determine compound concentrations that yielded 50% growth inhibition (IC 50 ), to allow detection of gene knockouts that cause sensitivity or resistance to each compound. As for other cell lines (Wagner et al 2017), ONC212 exhibited more potent activity than ONC201 in NALM-6 cells, with IC 50 values of 0.2 mM vs. 3.3 mM, respectively ( Figure 1C). Frequencies of sgRNA abundances before and after treatment were normalized to DMSO controls, and converted to gene-level scores by the RANKS algorithm (Bertomeu et al 2018).…”
Section: Loss Of Clpp and Mipep Confers Resistance To Onc201 And Onc212supporting
confidence: 56%
See 1 more Smart Citation
“…Dose-response curves of NALM-6 in the presence of ONC201 or ONC212 were generated to determine compound concentrations that yielded 50% growth inhibition (IC 50 ), to allow detection of gene knockouts that cause sensitivity or resistance to each compound. As for other cell lines (Wagner et al 2017), ONC212 exhibited more potent activity than ONC201 in NALM-6 cells, with IC 50 values of 0.2 mM vs. 3.3 mM, respectively ( Figure 1C). Frequencies of sgRNA abundances before and after treatment were normalized to DMSO controls, and converted to gene-level scores by the RANKS algorithm (Bertomeu et al 2018).…”
Section: Loss Of Clpp and Mipep Confers Resistance To Onc201 And Onc212supporting
confidence: 56%
“…20 phase II clinical trials for hematological malignancies and solid tumors (Allen et al 2016). Several mechanisms of action have been ascribed to ONC201 and its more potent derivate ONC212 (Wagner et al 2017), including: FOXO3A-mediated induction of TRAIL (Allen et al 2013) upon inhibition of the prosurvival AKT/ERK pathway (Allen et al 2013); activation of the integrated stress response (ISR) via the eIF2a kinases HRI and PKR, resulting in ATF4/CHOP-mediated upregulation of the TRAIL DR5 receptor (Kline et al 2016); activation of the ISR independent of eIF2a (Ishizawa et al 2016); and antagonism of dopaminergic G protein-coupled receptors (GPCRs) or activation of other GPCRs (Kline et al 2018;Madhukar et al 2019;Nii et al 2019;Prabhu et al 2019). Cell biological characterization suggests that ONC201 disrupts mitochondrial function and that cancer cells that do not depend on mitochondrial respiration are ONC201-insensitive (Greer et al 2018).…”
mentioning
confidence: 99%
“…Western blotting was performed as described previously (8,11,18). Briefly, lysates were prepared and evaluated with protein assay (Bio-Rad).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The imipridone class of anticancer compounds share a unique tri-heterocyclic core chemical structure (6) and selectively target GPCRs (7,8). ONC201 is the first imipridone to enter clinical trials (9) and is a selective antagonist of DRD2 and DRD3.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In this manuscript, Wagner et al aimed to identify novel, more potent compounds based on the original imipridone core structure of ONC201. 6 They manipulated substituents on the peripheral benzyl moieties and found that halide benzyl groups replacing the 2-methylbenzyl group at the R1 position produced compounds with much greater potency in cell viability assays than ONC201. Two compounds, ONC206 and ONC212, with sub-micromolar GI50 values in an expanded set of cell lines (GI50 values for ONC201 were between 1-10 uM) and wide therapeutic indices were further developed.…”
mentioning
confidence: 99%